Pendekatan Komunikasi Berasa; Empathy, Teo-Economic Dan Edukasi Kuliner Dalam Sistem Penginjilan Kristen Di Suku Hmong, Laos - Fetrie J.L Maramis; Endang Pasaribu (Riviera Publishing, 2025)
This article is a research conducted by the Global Glow Indonesia School of Theology (STTGGI) Jakarta as a mandate in implementing the Tri Dharma of Higher Education namely; Implementation of Education, Research and Community Service. The activity was jointly supported by the Christian University of Indonesia, Jakarta and the Word Partner Intersional Mission Agency on November 16-20, 2023 in the Hmong tribe and Vientine, the capital of Laos. The author explores through a felt communication approach the application of felt communication in the context of Christian evangelization in the Hmong tribe, Laos, with a focus on teaching healthy living and Indonesian cuisine. A sensory communication approach, which emphasizes sensory and emotional experiences, is used to deliver Christian messages more effectively and relevant to the Hmong culture. Through cooking demonstrations, practical health training, and hands-on interaction, this method creates a deep and meaningful experience. The study used qualitative methods with in-depth interviews and participatory observation to understand how this approach was received and interpreted by the Hmong community. The results show that empathetic communication enhances the understanding and acceptance of Christian messages in terms of healthy living and culinary as a nutritious food, while strengthening the relationship between missionaries and local communities.